PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA DI DESA MATTAMPAWALIE KECAMATAN LAPPARIAJA KABUPATEN BONE - Andika, Andika; Latang, Latang; Marzuki, Kartini (UNIVERSITAS NEGERI MAKASSAR, 2025)
This research examines community participation in ecotourism development in Mattampawalie Village, Lappariaja District, Bone Regency. The subjects of this research were 5 people consisting of 1 village head, 2 tourism managers and 2 community members. Data collected through observation, interviews and documentation. Data is processed through data reduction procedures, data presentation, and drawing conclusions and verification. The research results show that community participation in planning ecotourism activities can be beneficial from various aspects. While special working groups can be a driving force in planning and implementation, the development of local economic enterprises can also have a positive impact both economically and in the context of ecotourism sustainability. The level of understanding of the Mattampawalie Village community about the concept of ecotourism varies. There are residents who already have a fairly good understanding of ecotourism, identifying that it involves tourism that focuses on sustainability and nature conservation. On the other hand, there are also residents who do not fully understand the concept and want further explanation.